African cooking ware in the Algarve (Southern Portugal): an overview - Viegas, Catarina (Rei Cretariae Romanae Fautorum Acta, 2022)
Imports of African cooking ware in the Algarve region are very abundant and started appearing at the end of the 1st century AD, with the first forms of ARS A. The typological and contextual data shows that these imports lasted until the 5th century. In this paper we focus on the African cooking ware imports, to establish their position within the larger volume of traffic in African products (amphorae and ARS wares) during the early and the late Roman Empire. We present a re-evaluation of old assemblages, as well as some new data.